Design and Manufacturing Uncertainties in Cost Estimating within the Bid Process: Results from an Industry Survey - Parekh, S.; Roy, Rajkumar; Baguley, Paul (Cranfield University Press, 2009)
This paper discusses the issues of the bidding process with emphasis on the design and manufacturing uncertainties that can occur. The context of the paper is within manufacturing companies and in particular within the Defence sector. The paper presents the bidding process of a large Manufacturing company and details the main challenges and uncertainties that may occur. It also discusses the methods that are currently used to tackle uncertainty. The results of an industry survey compare the practices of other manufacturing companies and highlight the challenges at the bidding stage. The paper concludes that the development of an appropriate framework is necessary in order to effectively manage uncertainty at the bid stage.
Organised by: Cranfield University
Keywords: Bidding Stage; Cost Estimation; Uncertainty